THE EFFECT OF FERMENTATION TIME ON ANTIOXIDANT AND ORGANOLEPTIC ACTIVITIES OF BIDARA (Zizipus spina CRISTI L.) KOMBUCHA DRINK - Boima Situmeang; Muhammad Mutfi Amin Shidqi; Firman Rezaldi (Universitas Islam Negeri Ar-Raniry, 2022)
Bidara leaves contain antioxidants that are good for the body because they play a role in warding off free radicals. Kombucha made with bidara leaves is an innovative tea variant product that comes from the symbiotic culture of fermentation between bacteria and fungi. The purpose of this study is to determine the effect of fermentation time on antioxidant and organoleptic activity of kombucha and to determine the value of antioxidant activity of kombucha. The parameters measured were the antioxidant activity using the DPPH (2,2- diphenyl-picrilhydrazine) radical method and the organoleptic test with the hedonic scale including taste, aroma and color. The analysis showed that the length of fermentation time affected both the antioxidant activity and organoleptic test which included the taste, aroma and color of kombucha leaves of bidara. Based on the mean value of DPPH radical scavenging percentage, the antioxidant activity at fermentation time of 1, 8 and 12 days are 24,72%; 35,98%; and 7,05% with the highest antioxidant activity of kombucha made with bidara leaves occurred at 8 days fermentation is 35.87%. The IC50 value of kombucha made with bidara leaves product at fermentation time of 1, 8 and 12 days are 524,63 ppm; 441,03 ppm; and 1442,3 ppm Keywords: Antioxidant Activity, Kombucha, Leaf of Bidara, Organoleptic